UV Spectroscopic Method Development and Validation for the Estimation of Metformin HCL in Pure and Its Marketed Tablets - Rishika Vaishnav,; Vasavi Yadav,; N. Srinivasulu,; Y. Anand Kumar, (Asian Journal of Pharmaceutical Research and Development, 2025)
The present research study was to Ultra Violet spectroscopy (UV) method develop and validatefor the quantification of model anti-diabetic drug Metformin HCl (MET) in pure formand marketed tablets. Different solvent blends were screened blend comprising of Acetonitrile: Methanol: DW at 1:1:1was selected and same was used for study. The validation is done as per ICH guidelines, validated for their accuracy, precision and robustness of the chosen solvent blend. The results show the linearity in the concentration range (1-50 µg/mL) with correlation coefficient R2 = 0.9989 with percent recovery (100 – 101.5 %) with RSD was less than 2%, LOD and LOQ 0.0433, 0.132µg/mL respectively. This method can show high quality and there is no significant interference with the excipients and in pharmaceutical forms. None of the studies showed the development of this method before.